THE EFFECT OF GENRE-BASED MENTORING ON LINGUISTIC FEATURE QUALITY OF RESEARCH ARTICLE ABSRACTS BY INDONESIAN LECTURERS IN SOCIAL SCIENCES AND HUMANITIES - Dedi Jasrial; Safnil Arsyad; Arono Arono (Universitas Bengkulu, 2019)
Meta-discourse is one of the linguistic features that have gotten considerable attention in writing a research article abstract recently. It is because the meta-discourse serves as a textual and interpersonal marker that can help readers to organize, classify, interpret, evaluate, and react to the contents of a propositions or meanings of sentences in the research article abstracts. However, Indonesian authors still have a problem in the use of meta-discourse based on its function in writing a research article abstract that meets to reputable international journals. The purpose of this study is to help improve the linguistic feature quality of research article abstracts written by Indonesian lecturers in social sciences and humanities in terms of the appropriate use of meta-discourse devices. This study used three stages of genre-based method following Hyland (2003): modeling, joint construction, and independent construction to mentor 20 lecturers in improving their research article abstract quality in terms of the appropriate use of meta-discourse devices in the sentences. The meta-discourse devices in the lecturers’ research article abstracts was evaluated following the frameworks of meta-discourse based on its function as suggested by Hyland (2005). The result revealed that there is an important improvement on the linguistic feature quality of Indonesian lecturers’ research article abstracts in terms of the appropriate use of meta-discourse devices. It implies that genre-based mentoring method has been quite effective in helping Indonesian lecturers in social sciences and humanities in writing their RA abstracts in using meta-discourse devices for a reputable international journal.